The Nexus Between Intangible Assets and Firm Performance: Evidence From A Developing Economy - Özcan, Ahmet (Contemporary Business and Economic Issues II, 2023)
The global economic crisis significantly increased the importance of intangible assets. Intangible assets are considered a crucial component of firm reserves. The aim of this book chapter is to investigate whether intangible assets have an impact on financial performance using a panel of non-financial firms listed in the Istanbul Stock Exchange 30. The results of the panel data analysis reveal a statistically significant and positive relationship between intangible assets, return on equity, and financial performance. Küresel ekonomik ortamda, maddi olmayan varlıkların önemi büyük ölçüde arttı. Maddi olmayan varlıklar firma bilançolarının önemli bir bileşeni olarak görülmektedir. Bu kitap bölümünün amacı, Borsa İstanbul 30 endeksinde yer alan finansal olmayan firmaları içeren bir örneklem kullanarak, maddi olmayan varlıkların finansal performans üzerindeki etkilerini araştırmaktır. Panel veri analizinin sonuçları, maddi olmayan varlıklar ile özsermaye karlılığı ile ölçülen finansal performans arasında istatiksel olarak anlamlı ve pozitif bir ilişki olduğunu ortaya koymaktadır.